Regulatory Science to 2025: An Analysis of Stakeholder Responses to the European Medicines Agency's Strategy - Hines, Philip A.; Gonzalez-Quevedo, Rosa; Lambert, Apolline I. O. M.; Janssens, Rosanne; Freischem, Barbara; Torren Edo, Jordi; Claassen, Ivo J. T. M.; Humphreys, Anthony J. (Frontiers in Medicine, 2020)
The pace of innovation is accelerating, and so medicines regulators need to actively innovate regulatory science to protect human and animal health. This requires consideration and consultation across all stakeholder groups. To this end, the European Medicines Agency worked with stakeholders to draft its Regulatory Science Strategy to 2025 and launched it for public consultation. The responses to this consultation were analysed qualitatively, using framework analysis and quantitatively, to derive stakeholders’ aggregate scores for the proposed recommendations. This paper provides a comprehensive resource of stakeholder positions on key regulatory science topics of the coming five years. These stakeholder positions have implications for the development and regulatory approval of both human and veterinary medicines.